TO STUDY DIFFERENT MODALITY OF DIAGNOSING BLUNT INJURY TO ABDOMINAL SOLID ORGAN INJURY MANAGEMENT - Dr. Vasant Dakwale (International Journal of Medical Science And Diagnosis Research, 2019)
Background: All Solid Organ Injury of Abdomen of above 14 yr age group by blunt trauma admitted in routine & emergency hours in General Surgery in Index Medical College Hospital & Research Centre, Indore, in duration June 2017 – June 2018 with the help of the residents surgical officer looking after the admitted patients as prospective analysis with solid organ injury. Etiology & Mechanism of blunt abdominal injuries Causative agent Include patient who sustained injury due to- RTA, Assault by Fists and blows, Lathy, Iron rods, Kicks. Received accidental animal kicks over abdomen, Got injured due to fall of some heavy object like log, gravel, got buried in mine. Results: In 26 Laparotomy patients in blunt abdomen injury there were 100 Internal Organ injuries founded. Among these injuries Hemoperitoneum, 22 cases i.e.22% was the most common, Intra-operative finding in BAT patient. Liver injury 57 cases i.e.57 % was most common abdominal solid organ injury in BAT patient and pancreas is least common 10 cases. i.e.10% Involved abdominal solid organ in BAT. In solid organ injury there were maximum incidence of liver injury 57 cases. I.e. 57 % followed by spleen 47 cases i.e.47% and kidney16 cases. i.e. 16%. Conclusion: In abdomen solid organ injury there was maximum incidence of liver injury 57%, followed by spleen injury. 47%, followed by renal injury 16% and followed by pancreatic injury cases 10% involved in BAT. Abdominal solid organ injury grading and management according to AAST guideline (based on CT finding). In our study, tried to develop the management protocol for patients with clinical examination and findings. Keywords: Modality, Diagnosis, Blunt Injury & Abdominal Solid Injury.